Violent Behavior During Psychiatric Inpatient Treatment in a German Prison Hospital - Seidel, P.; Konrad, N.; Negatsch, V.; Dezsö, D.; Kogan, I.; Gauger, U.; Neumann, B.; Voulgaris, A.; Opitz-Welke, A. (Frontiers in Psychiatry, 2019)
Violent behavior in correctional facilities is common and differs substantially in type, target, implication and trigger. Research on frequency and characteristics of violent behavior in correctional facilities and psychiatric hospitals is limited. Results from recent research suggest that comorbidity of severe mental disorder, personality disorder and diagnosis of substance abuse is related to a higher risk of violent behavior. In the Berlin prison hospital, a database was created to collect data from all violent incidences (n=210) between 1997 and 2006 and between 2010 and 2016. In a retrospective, case control study, specific socioeconomic data and psychiatric diagnosis were analyzed. We compared the group of prisoners with violent behavior with randomly selected prisoners of the same department without violent behavior (n=210). Parenthood, using a language interpreter and previous sentences were associated with non-violent patients. There were no significant differences regarding age, diagnosis or legal status. Practical implications for clinical work are discussed.